Prevalence of R Genes for Resistance to Potato Viruses in Uganda Germplasm - Byarugaba, Arinaitwe Abel; Mukasa, Settumba B.; Barekye, Alex; Rubaihayo, Patrick R. (Potato Research, 2021)
The most important potato viruses in Uganda are Potato virus Y (PVY), Potato leaf roll virus (PLRV), Potato virus X (PVX), Potato virus S (PVS), Potato virus A (PVA) and Potato virus M (PVM). Utilization of R genes in breeding for resistance to viruses has not been explored in Uganda due to limited information on the prevalence of R genes in the available genotypes. This study aimed at identifying potato genotypes with R genes for resistance to potato viruses important in Uganda. The study screened 71 potato accessions from the National Potato Breeding Programme at Kachwekano Zonal Agricultural Research and Development Institute for the presence of resistance genes to viruses using diagnostic molecular markers. The results indicated that 21 out of 71 genotypes had resistance markers, of which nine genotypes, NKRN59.58, Derby, Markies, Sifra, 395017.229, Nakpot 5, 20108.5, Royal and 393220.54, had Ryadg gene for PVY resistance and two genotypes, Kimuri and 319919.3, had Rysto gene for resistance to PVY and PVA. Nine genotypes, 395011.2, Markies, Nakpot 5, 20108.5, Sifra, 20157.6, Royal, 2015.8 and Ambition, had the Nbtbr gene for resistance to PVX. In addition, 14 genotypes, 395011.2, Markies, Nakpot 5, Sarpouna, 393220.54, 391046.14, Sarpomira, 395077.12, Sifra, 20157.6, Royal, Ambition, Kimuri and Caruso, had the Nsadg gene conferring resistance to PVS. Four genotypes, Markies, Sifra, Nakpot 5 and Royal, had the Ryadg, Nbtbr and Nsadg genes for combined resistance to PVY, PVX and PVS. The resistant genotypes could be used as parents to introgress resistance genes into susceptible cultivars.
Keywords: Allele-specific markers; Molecular markers; Potato viruses; R genes; Virus resistant genotypes